LEAN POLYCLINIC: REGIONAL EXPERIENCE OF PARTICIPATION OF MEDICAL ORGANIZATIONS IN THE PILOT PROJECT "FORMATION OF MODELS OF PRIMARY CARE ORGANIZATION BASED ON THE PRINCIPLES OF VALUE-BASED HEALTHCARE" - Виктория Владимировна Голошубина; Зульфия Байтуяковна Тасова; Дмитрий Иванович Трухан (Медицина в Кузбассе, 2023)
The goals and basic principles of the concept of value-based healthcare are described. The experience of participation of medical organizations of the Omsk Region in the implementation of the pilot project "Formation of models of primary care organization based on the principles of value-based healthcare" is analyzed. During the implementation of the project, 9 processes are researched and improved, key performance indicators are identified. It is concluded that the transition to value-based healthcare will improve the quality of medical care.